Over-the-Counter-Drugs for the Treatment of Mood and Anxiety Disorders – The Views of German Pharmacists - Hamann, J.; Linde, K.; Schweiger, H.-D.; Kusmakow, O.; Förstl, H. (Pharmacopsychiatry, 2014)
Introduction: Depression, anxiety, agitation and sleep disorders are highly prevalent in the general population, but few persons receive psychiatric care.Methods: Our aim was to study the views of 690 German pharmacists on “over-the counter” (OTC) drugs for these indications.Results: They reported dispensing OTC medication to an average of 12 customers per day, and this corresponded to almost one quarter of the medications provided for these indications. Herbal drugs and complex homeopathic formulations were used most frequently. Patients preferring OTC substances were described as being younger, with shorter durations of illness and less severe symptoms, and more skeptical regarding psychopharmacology. While genuine pharmacological effects were considered as most relevant, pharmacists were highly aware of placebo and interpersonal factors. Symptoms, comorbidity and advice on drug intake were prominent topics during pharmacy consultations.Conclusion: German pharmacists report dispensing large amounts of OTC drugs for anxiety, agitation, sleep disturbances or depression. It is unclear whether this constitutes a rational and cost effective method to deal with mild courses of high prevalence diseases or must be seen critically.
Keywords: anxiety disorders; depression treatment; drug-seeking behavior